2019
DOI: 10.1186/s12879-019-4609-8
|View full text |Cite
|
Sign up to set email alerts
|

A changing profile of infective endocarditis at a tertiary hospital in China: a retrospective study from 2001 to 2018

Abstract: BackgroundInfective endocarditis (IE) is a lethal disease which has been changing significantly over the past decades; however, information about IE in China remains scarce. This study surveyed the changes in clinical characteristics of IE at a tertiary hospital in south China over a period of nearly 18 years.MethodsMedical records with IE patients consecutively hospitalized between June 2001 and June 2018 were selected from the electronic medical records system in Nanfang Hospital of Southern Medical Universi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(64 reference statements)
3
7
0
Order By: Relevance
“…In the present study, blood cultures were negative in 56.7% of cases, similar to the data in some Asiatic populations (30–61%) 32–34 but surpassing the number in other developed countries (7–20%). 33 , 35 , 36 The high prevalence of negative blood cultures was usually associated with the antibiotic treatment given before the blood culture, the insufficient number of blood cultures submitted, highly fastidious bacterial or nonbacterial infections, and inadequate microbiological techniques.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, blood cultures were negative in 56.7% of cases, similar to the data in some Asiatic populations (30–61%) 32–34 but surpassing the number in other developed countries (7–20%). 33 , 35 , 36 The high prevalence of negative blood cultures was usually associated with the antibiotic treatment given before the blood culture, the insufficient number of blood cultures submitted, highly fastidious bacterial or nonbacterial infections, and inadequate microbiological techniques.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also attempted to explore the effect of blood culture results on the accuracy of echocardiographic diagnosis of IE, but the results were not satisfactory. In our previous study [ 11 ], we mentioned that the blood culture positive rate of IE in our hospital was only 58.2% due to antibiotic abuse and other reasons, which was roughly consistent with the results of the present study. We speculated that this might affect the univariate analysis results.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies pointed out that surgery was independently associated with a lower risk of in-hospital mortality [ 13 15 ]. We previously performed a multivariate analysis in 313 cases of IE (including prosthetic valve endocarditis) [ 11 ] and identified intravenous drug addiction, prosthetic valve endocarditis, hemorrhagic stroke, acute congestive heart failure, renal insufficiency, left-sided endocarditis, and early surgery as independent predictors of in-hospital mortality. According to this data, we concluded that the surgery and less frequent occurrence of hemorrhagic stroke were protective factors for good prognosis of IE in the surgery group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, four patients had a fever on admission, but none fulfilled the modified Duke criteria as a definite or suspected case for infectious endocarditis. 10,11 Only 2 of 10 patients had increased prosthetic mitral valve gradients without significant transvalvular or paravalvular leakage. The two patients also had no apparent vegetation in transthoracic echocardiography.…”
Section: Discussionmentioning
confidence: 99%